Education and Human Resource Management in Driving National Economic Growth - Sari, Cindi Permata; Manan, Afni Abdul; Zani, Risma; Sulaiha, Sulaiha; Almustaqin, Almustaqin (Jurnal Ilmiah Teunuleh, 2025)
The role of education and human resource (HR) management in supporting national economic growth, especially amidst the challenges of globalization and digital transformation. The objective of this research is to identify and analyze strategies for developing education and HR that can drive Indonesia's economic progress. The method employed is a Systematic Literature Review (SLR) using content analysis of relevant studies concerning education, HR development, and their impact on the economy, particularly in the Micro, Small, and Medium Enterprises (MSME) sector. The results show that education especially vocational education and industry-based training plays a vital role in enhancing workforce skills aligned with labor market demands. Additionally, the integration of technology and digitalization in HR management contributes to increased efficiency and productivity. The conclusion of this study suggests that improving the quality of education, strengthening vocational training, and leveraging technology in HR systems should be prioritized in national economic development strategies. Synergy between the government, educational institutions, and industries is essential to create competitive and high-quality human capital on a global scale.